Dampak Perkembangan Podcast serta Penyebab Berkurangnya Peminat Radio Tradisional - Rambe, Ahmad Sampurna; Diva, Dwi Dini Farah; Wahyuni, Rizki Cahya; Nurizain, Ayu; Lubis, Sabila Husna; Sakinah, Nina Kurnia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The development of technology and information has been proven by the emergence of new media that is increasingly massive. One of them is podcasts, digital audio documents uploaded online to be shared with the public. Podcasts are considered an alternative to radio, and in 2016, Nielsen predicted that 2020 would be the beginning of a "new golden age of audio". This prediction has proven to be true, with the number of podcast listeners in Indonesia tripling in 2020. In April 2022, Indonesia even ranked second as the country with the most podcast listeners in the world. However, the increasingly dominant development of podcasts has actually had an impact on the decline in interest and listeners of traditional radio. In this regard, researchers will investigate the impact of the development of podcasts on traditional radio, as well as the causes of decreased interest in traditional radio, especially in Indonesia.